SMALL AREA ESTIMATION OF CHILD UNDERNOURISHMENT PREVALENCE IN BALI AND NUSA TENGGARA - Nuriyo, Amalia Ndaru; Fajar, Huda Muhammad; Novaldi, Jeremia; Rahmi, Meautia; Miswa, Sabrina Do; Sumarni, Cucu (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2025)
Children under the age of 17 are particularly prone to undernutrition. Undernutrition can impair children’s growth and development. In the process of policy formulation, it is necessary to calculate a reliable estimate of the prevalence of child undernourishment at the smallest level possible. Using the data of SUSENAS 2023 from BPS, direct estimates at the regency/city level in Bali, West Nusa Tenggara (NTB), and East Nusa Tenggara (NTT) have relative standard error values of over 25% (RSE > 25%), making them less reliable for usage. To solve this, an indirect estimating method known as small area estimation (SAE) can be applied. This study employs SAE HB Lognormal to estimate the prevalence of undernutrition in children. The results of this study show that small area estimation using the HB Lognormal approach improved the reliability of estimates (RSE) of the prevalence of undernutrition in children at the regency/city level in Bali, NTB, and NTT.